Effect of topical immunotherapy with squaric acid dibutylester for alopecia areata in Japanese patients - Keisuke Sakai; Satoshi Fukushima; Satoru Mizuhashi; Masatoshi Jinnin; Takamitsu Makino; Yuji Inoue; Hironobu Ihn (Allergology International, 2020)
Background: The Japanese guidelines for the treatment of alopecia areata list topical immunotherapies as a drug therapy for this condition. However, there is insufficient evidence of its efficacy to support this recommendation. Thus, we sought to clarify the effect of topical immunotherapy on the progression and severity of alopecia areata in Japanese patients. Methods: To evaluate the effect of topical immunotherapy with squaric acid dibutylester (SADBE) in alopecia areata patients, we performed a retrospective cohort study on 49 alopecia patients who had received topical immunotherapy with SADBE. Patients were evaluated by the change in alopecia severity at 6 and 12 months after the initiation of topical immunotherapy. The improvement rate was calculated by determination of the complete and partial responses rate to treatment with topical immunotherapy by application of SADBE. Results: The improvement rate in all alopecia patients treated with SADBE topical immunotherapy was 57.8% (complete response; 11.1% and partial response; 46.7%). Conclusions: Topical immunotherapy with SADBE is an effective treatment for alopecia areata. Therefore, the current treatment recommendations for alopecia areata with topical immunotherapies are appropriate. Keywords: Alopecia, Cohort study, Severity, Topical immunotherapy, Response rate